Non-seminomatous germ cell tumor with bone metastasis only at diagnosis: A rare clinical presentation - K.C. Biebighauser; Jianjun Gao; Priya Rao; Gene Landon; Lance Pagliaro; Colin P.N. Dinney; Jose Karam; Neema Navai (Asian Journal of Urology)
Bone metastasis of non-seminomatous germ cell tumors (NSGCT) of the testes is a rare event and even more uncommon at initial presentation. Generally, bone lesions are discovered in the presence of concurrent retroperitoneal lymph node or visceral disease. However, in this case, a 37 years old male complaining of a growing testicular mass was found to have isolated bone metastasis with associated caudaequina syndrome without apparent abnormal findings on initial computed tomography (CT) scans. Continued neurologic symptoms prompted further evaluation with magnetic resonance imaging (MRI), which demonstrated multiple sites of bone metastasis without evidence of retroperitoneal lymph node or visceral organ involvement. This case represents a rare clinical presentation and disease manifestation of NSGCT.